The Analysis of Hero’s Journey in the Unlikely Hero Hiccup from How to Train Your Dragon (2003) - Biova Kusuma; Rina Saraswati; Nur Wulan (Lakon : Jurnal Kajian Sastra dan Budaya, 2026)
Hero’s journey is a theory that unveils the narrative structure and process of becoming a hero. Christopher Vogler argues that the structure and pattern of becoming a hero is often depicted in contemporary literature and one of them is How To Train Your Dragon (2003) novel. This research is trying to discover the twelve stages of Hiccup’s journey in Christopher Vogler’s theory that mapped throughout the narrative. Not only that, this research also uses the archetype theory by Christopher Vogler depicted in Hiccup’s journey as a hero and trickster archetype that successfully operates in his journey. This research is using the textual analysis method and close reading to find the evidence substantially and essentially, so that hopefully this research could contribute to future research on How To Train Your Dragon (2003) novel and literature, especially hero’s journey.